Enhancing Seedling Growth and Budding Potential in Ber (Zizyphus mauritiana) Using Gibberellic Acid and Bacterial Inoculants - GULAB PANDOVE; NAVJOT GUPTA (Seed Research, 2025)
Indian jujube (Zizyphus mauritiana Lamk.), commonly known as ber, is a commercially significant fruit in arid and semi-arid regions of India due to its high returns, low input costs, and drought tolerance. However, delayed budding in ber rootstock seedlings often results in unbuddable plants, leading to resource wastage. This study aimed to enhance vegetative growth in ber rootstock under nursery conditions using gibberellic acid (GA3) and liquid bacterial inoculants (LBIs) of Sphingobacterium sp. and Azotobacter sp. A field experiment was conducted at PAU, Regional Research Station, Bathinda, using a randomized complete block design with five treatments. Seedlings treated with the combined LBIs showed significant improvements in shoot number (27.45%), shoot length (21.04%), collar diameter (29.63%), root length (17.65%), and biomass accumulation compared to control.Enhanced growth is attributed to increased nutrient availability and phytohormone production by inoculated bacteria. Although microbial counts in rhizospheric soil increased numerically in treated plants, the changes were statistically non-significant. The findings suggest that LBIs can effectively improve rootstock growth, making seedlings suitablefor timely budding and reducing wastage. Future studies should assess budding success and conduct biosafety evaluations of the microbial strains, alongside soil biofertilizer applications to improve long-term soil health and productivity